Dimensionamento da pasteurização para a obtenção de um caldo de cana destinado à produção de frozen de cana: um estudo de caso - Oka, Yasmin Naomi Gushiken (Universidade Federal de São Carlos, 2025)
Sugarcane juice, also known as "garapa," is a traditional beverage widely consumed in Brazil, especially at open-air markets, and is obtained by extracting the liquid from sugarcane stalks. Aiming to diversify its consumption, a startup developed the concept of frozen sugarcane juice, in which the freshly extracted juice is immediately frozen to extend its shelf life. However, this process does not fully ensure the product’s quality and safety, and it requires thawing before being processed in the frozen beverage equipment. In this context, the present study aimed to evaluate the feasibility of applying pasteurization as an alternative to freezing, allowing shelf life extension, while maintaining microbiological safety and improving process efficiency. To achieve this, a fictional heat exchanger was designed and dimensioned for the pasteurization of raw sugarcane juice, using thermodynamic calculations and physical-chemical parameters. The proposed plate heat exchanger demonstrated thermal efficiencies ranging from 77% to 81%, values consistent with technical references. It is concluded that the adoption of pasteurization, supported by the use of plate heat exchangers, presents a promising alternative for the sugarcane juice processing industry, offering benefits in both food safety and operational cost reduction.
Dimensioning of pasteurization for the production of sugarcane juice intended for frozen cane: a case study
Keywords: Tratamento térmico; Otimização de processos; Trocador de calor a placas; Eficiência; Thermal treatment; Process optimization; Plate heat exchanger; Efficiency; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS